2014
DOI: 10.1007/s00726-014-1772-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with essential amino acids boosts the beneficial effects of rosuvastatin on mouse kidney

Abstract: The effects of high-potency statins on renal function are controversial. To address the impact of statins on renal morpho-functional aspects, normotensive young mice were treated with rosuvastatin (Rvs). Moreover, because statins may impair mitochondrial function, mice received either dietary supplementation with an amino acid mixture enriched in essential amino acids (EAAm), which we previously demonstrated to increase mitochondrial biogenesis in muscle or an unsupplemented control diet for 1 month. Mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 80 publications
(95 reference statements)
7
20
0
Order By: Relevance
“…The main message from our data is that the EAA-rich diet could improve spleen health of aged animals by reducing inflammation and by increasing chaperones and cell survival markers. Similar results have already been reported in muscles, liver, heart and kidneys [19,21,23,25] but to our knowledge, it is the first time that these results have been reported in the far less considered spleen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The main message from our data is that the EAA-rich diet could improve spleen health of aged animals by reducing inflammation and by increasing chaperones and cell survival markers. Similar results have already been reported in muscles, liver, heart and kidneys [19,21,23,25] but to our knowledge, it is the first time that these results have been reported in the far less considered spleen.…”
Section: Discussionsupporting
confidence: 91%
“…We have shown that aged mice with a diet supplemented with a balanced EAA formulation increases lifespan, improves mitochondrial biogenesis and morphological and molecular changes in the heart, skeletal muscle and adipose tissues [19,20,21,22]. The protective role of an EAA rich diet was also observed in rat livers with chronic ethanol consumption [23,24], in the kidneys of rosuvastatin-treated mice [25] and during wound healing [26]. Furthermore, in vitro data showed that variations in the EAA/NEAA concentration ratio regulates cancer cell survival or death [27].…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that excess EAAs possesses anti-inflammatory properties. This is in line with our previous studies showing that dietary supplementation with balanced EAAs mixtures reduced oxidative stress, thus slowing cellular aging [3,5,7,9]. This is also confirmed by our newlycompleted lifespan experiment showing that weaned male mice fed with EAA-rich diets live longer (about over 10%) than those fed StD (25 vs 22 months respectively).…”
Section: Neaa-exsupporting
confidence: 80%
“…1) The EAA-exclusive diet (EAA-Ex) contained EAAs (100%) as the unique source of N, in a formulation tailored to mammal needs [14] and widely applied in clinical and experimental studies [3,5,7,9,10,15].…”
Section: Diet Compositionmentioning
confidence: 99%
“…Moreover, the ROS defense genes were upregulated, and ROS production was reduced [99]. EAA supplementation was also effective in reducing damage caused by alcohol in the liver and by rosuvastatin in the kidney [146,147]. Together, these studies offer a rationale for exploring the role of EAA in preventing and controlling chemotherapy-induced toxicity.…”
Section: Oral Supplementation Of Special Mixture Of Aminoacids Maintamentioning
confidence: 97%